2023
DOI: 10.3390/ijms24097792
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-1 Knockout and Rescue Confirms Its Role to Promote Metastasis in MDA-MB-231 Breast Cancer Cells

Abstract: Breast cancer (BC) metastasis remains a leading cause of female mortality. Neuropilin-1 (NRP-1) is a glycoprotein receptor that plays ligand-dependent roles in BC. Clinical studies indicate its correlation with metastatic disease; however, its functional role in BC metastasis remains uncertain. CRISPR-Cas9 was used to knockout the NRP-1 gene in MDA-MB-231 BC cells, and the effects on metastasis were determined using an orthotopic mouse engraftment model. NRP-1 expression in knockout cells was rescued using a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…The ECM-receptor interaction signaling pathway plays an important role in tumor shedding, adhesion, degradation, movement, and proliferation ( Bao, et al, 2019 ; Huang, et al, 2024 ). The role of ECM in other cancers has also as well been discovered ( Cui, et al, 2018 ; Yan, et al, 2018 ; Zhang, et al, 2022 ; Al-Zeheimi, et al, 2023 ). However, the ECM-receptor interaction signaling pathway has also been found to play an important role in feather follicle development.…”
Section: Discussionmentioning
confidence: 98%
“…The ECM-receptor interaction signaling pathway plays an important role in tumor shedding, adhesion, degradation, movement, and proliferation ( Bao, et al, 2019 ; Huang, et al, 2024 ). The role of ECM in other cancers has also as well been discovered ( Cui, et al, 2018 ; Yan, et al, 2018 ; Zhang, et al, 2022 ; Al-Zeheimi, et al, 2023 ). However, the ECM-receptor interaction signaling pathway has also been found to play an important role in feather follicle development.…”
Section: Discussionmentioning
confidence: 98%
“…Zhang et al [30] reported that the activation of the ECM receptor interaction pathway can promote hepatocellular carcinoma proliferation and invasion. In breast cancer, the ECM-receptor interaction pathway plays an important role in cancer progression and metastasis [31] . The important functions of the ECM-receptor interaction pathway in sarcoma have also been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…These specific domains participated in different signaling pathways and versatile roles controlling survival, migration, and invasion, as well as angiogenesis and axon guidance, through binding ligands to co-receptors, including VEGF and semaphorin family members [3,4]. For example, in breast cancer cells MDA-MB-231, CRISPR-Cas9 knocking out the NRP1 gene was reported to have a pronounced reduction in lung metastasis [6].…”
Section: Introductionmentioning
confidence: 99%